Nanotechnology - the next wave - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Mohamad Najib, Mohammad Nor (Penerbit UMP, 2008)
Nanotechnology is defined as the engineering of functional systems at the molecular scale.